HUBUNGAN ANTARA INISIASI MENYUSU DINI DENGAN KEJADIAN HEMORAGIA POSTPARTUM BPS SITI QUNI ELIZABETH, SST KECAMATAN TAPEN KABUPATEN BONDOWOSO - Khusniyati, Etik; Merna Nur Intan Lestari, Hj. (JURNAL KEPERAWATAN BINA SEHAT, 2015)
The Government of Indonesia supports policy of WHO and Unicef recommending initiation of milk early (early latch on) as action life saving. In reality in field initiation of milk early fail to with reason of not had the heart to see its (the baby weeps, so that initiation of milk early fails executed. This thing causing the happening of haemorrhage postpartum as result of not implementation of initiation of milk early. This research done to know relation between initiation of milk early with case of haemorrhage postpartum in Ny Siti Quni Elizabeth, Bondowoso. This research uses design cross sectional. The population is all mother birthing in Ny Siti Quni Elizabeth, SST , Bondowoso. Sampling technique is a non probability sampling type consecutive sampling, with 41 responders. Research variable is independent that is giving of initiation of milk early and variable dependen that is case of haemorrhage postpartum. Data is obtained by the way of observation. Result of research shows there is relationship which bermakna/signifikan between milk initiations early with case of haemorrhage postpartum, with test Chi Square (χ2) got result : χ2calculate > χ2tables = 12,256 > 3,84. Results of the study that mothers who do not gives initiation of milk early are likely to experience postpartum bleeding, because there is no stimulation of the infant to stimulate the release of oxytocin, which helps stop bleeding naturally.Keyword : initiation of milk early, haemorrhage postpartum